BOARD CHARACTERISTICS AND OPERATIONAL EFFICIENCY OF WATER AND SANITATION COMPANIES IN MOUNT KENYA REGION - Mugambi Joyce Wanjiru; Douglas Rosana; Tumaini Mwikamba (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
Board characteristics have become a significant area of scholarly inquiry in both developing and developed economies, as they reflect the relationship between directors and stakeholders. This study aimed to examine the relationship between board characteristics and the operational efficiency of water and sanitation companies in the Mount Kenya Region. Specifically, it assessed the effects of board size, board diversity, board competence, and board meeting frequency on operational efficiency. The study was grounded in agency theory, stewardship theory, stakeholder theory, and transaction cost theory, and adopted a quantitative research design. A census approach was used, covering all 21 water and sanitation companies in the region. Secondary data were collected from financial statements for the period 2019–2024. Panel data regression analysis was employed to evaluate the relationships between variables. The findings revealed that all board characteristics examined have a positive and statistically significant effect on operational efficiency. Board size showed the strongest influence (β = 0.350), followed by board meeting frequency (β = 0.299), board diversity (β = 0.283), and board competence (β = 0.180). The study concludes that board characteristics play a crucial role in enhancing organizational efficiency. It recommends that organizations prioritize appropriate board composition by improving member qualifications, optimizing board size, promoting diversity, and ensuring regular meetings. These measures are essential for strengthening governance and improving operational performance in water and sanitation companies.